2017
DOI: 10.1111/bdi.12588
|View full text |Cite
|
Sign up to set email alerts
|

Patients with chronic bipolar disorder exhibit widespread increases in extracellular free water

Abstract: Our study suggests that chronic BP shows similar WM changes to early SZ, suggesting that extracellular FW increases could be a transient indication of recent psychotic episodes. Since FW increase in SZ has been suggested to be related to neuroinflammation, we theorize that neuroinflammation might be a shared pathology between chronic BP and early SZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Interestingly, a study of 17 individuals with BD1 and 28 controls reported that individuals with chronic bipolar disorder look most similar to schizophrenia patients in their first episode, in that the chronic BD group showed global FW increases, but no significant FA T decreases, compared to controls (Tuozzo et al, 2017). Tuozzo et al (2017) interpreted these findings as indicative of a globalized acute response, possibly inflammation, in BD.…”
Section: A Survey Of Advanced Microstructural Diffusion Mri Studies Imentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a study of 17 individuals with BD1 and 28 controls reported that individuals with chronic bipolar disorder look most similar to schizophrenia patients in their first episode, in that the chronic BD group showed global FW increases, but no significant FA T decreases, compared to controls (Tuozzo et al, 2017). Tuozzo et al (2017) interpreted these findings as indicative of a globalized acute response, possibly inflammation, in BD.…”
Section: A Survey Of Advanced Microstructural Diffusion Mri Studies Imentioning
confidence: 99%
“…Interestingly, a study of 17 individuals with BD1 and 28 controls reported that individuals with chronic bipolar disorder look most similar to schizophrenia patients in their first episode, in that the chronic BD group showed global FW increases, but no significant FA T decreases, compared to controls (Tuozzo et al, 2017). Tuozzo et al (2017) interpreted these findings as indicative of a globalized acute response, possibly inflammation, in BD. No correlations were found between free-water measures and clinical scores, however, suggesting that changes in extracellular free-water do not impact clinical presentation, but rather reflect an up- or down-stream process related to the central neuropathology of the disorder.…”
Section: A Survey Of Advanced Microstructural Diffusion Mri Studies Imentioning
confidence: 99%
“…Additional studies using independent datasets have replicated this dual-mechanism underlying WM abnormalities in FEPs (Lyall et al, 2018). Tuozzo et al (2018) reported widespread higher FW in chronic BD but no significant FA-t changes compared to controls. FW DTI may also shed light on discrepant results of WM microstructural abnormalities previously reported in studies of FEPs using traditional FA.…”
Section: Introductionmentioning
confidence: 98%
“…Free water maps therefore seem promising for mapping degenerated spaces. FWE-DTI metrics have demonstrated significantly higher test-retest reliability than conventional DTI parameters (Albi et al, 2017), and have already provided insight on microstructural brain changes in conditions such as Alzheimer’s disease (Maier-Hein et al, 2015), depression (Bergamino et al, 2016), schizophrenia (Mandl et al, 2015), Parkinson’s disease (Ofori et al, 2015), Huntington’s disease (Steventon et al, 2016), and bipolar disorder (Tuozzo et al, 2017). Importantly, FWE-DTI does not require custom data acquisitions and can be applied post-acquisition to any DTI sequence.…”
mentioning
confidence: 99%